Membangun Sistem Informasi Presensi Kuliah Berbasis NFC di Prodi Informatika Unjani Yogyakarta - Hisanah, Iklil; Himawan, Arif; Rahmawati, Titik; Alfi Sa'diya, Nafisa (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2020)
The Unjani Yogyakarta campus, specifically the Informatics Study Program, currently relies on manual methods such as calling students individually or using journal book signatures for attendance. This approach has drawbacks, including flexible attendance time, time-consuming procedures, and potential disruptions to student focus during lectures. To address these issues, the author conducted research to develop a student attendance information system for the campus. The system utilizes a client-server architecture and incorporates NFC technology on Android smartphones and RFID cards. The research aims to establish fixed attendance times and enable digital attendance through Android devices. It also facilitates monitoring of lecture activities for program administrators by integrating mobile and web applications. The system, developed using JAVA for mobile clients and PHP with CodeIgniter and Bootstrap for the web server, was built using the Research and Development method. The resulting student attendance application streamlines the attendance process for program administrators and lecturers. However, it should be noted that the system relies heavily on an internet connection and can serve as an alternative for online classroom attendance.